Production of lignin from coconut husk - Balmaceda, Estela; Carpio, Denis; Benito, Corazon Pe. (Quezon City College of Engineering, 1965)
Capacity: 6 tons per day -- Land area: 39,700 sq.m. -- Fixed capital investment: 10,133,301.50 -- Operating cost at maximum production: 4,968,339.90 -- Annual sales at maximum production: 6,626,000.00 -- Pay-off period: 3.8 years -- Maximum annual rate of production: 2,450 tons -- Break-even point: 27% (660 tons) -- Shut-down point: 24% (598 tons) -- % Return on investment: 16.32%
Typescript.
Submitted in partial fulfillment of the requirements in ChE 62.
Keywords: Factories -- Design and construction; Factories -- Design and construction; Lignin; Coconut